2017
DOI: 10.1016/j.sjopt.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Retinal nerve fiber layer thickness in children with β-thalassemia major

Abstract: In this study, we observed RNFL was thinner in patients with β-thalassemia major. Thinning of RNFL did not correlate with hemoglobin or ferritin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
1
6
3
Order By: Relevance
“…Sex distribution among the study population was found to corroborate with various previous studies [13][14][15].…”
Section: Gender Distributionsupporting
confidence: 90%
See 1 more Smart Citation
“…Sex distribution among the study population was found to corroborate with various previous studies [13][14][15].…”
Section: Gender Distributionsupporting
confidence: 90%
“…Mean age of this study population was much higher (23.6 years) compared to other studies like by Uzun et al [13] where the mean age of the study population was much younger (average 13.7 years).…”
Section: Age Distributioncontrasting
confidence: 64%
“…As a result, various ocular manifestations can be seen in β-thalassemia patients including color vision anomalies, night blindness, cataract, visual field defects, decreased visual acuity, and optic neuropathy. 1 We did not find any eye findings to be detected yet in our study patients.…”
Section: Discussioncontrasting
confidence: 64%
“…β-thalassemia syndromes include a group of hereditary blood disorders characterized by the development of anemia as a result of a combination of hemolysis, ineffective erythropoiesis, and iron overload due to defective β-globulin chain synthesis. 1 The World Health Organization reports that thalassemia is the most common chronic and genetic disease in 60 countries and affects about 10,000 people per year. 2 Intensive chronic anemia, growth retardation, bone disorders, hepatosplenomegaly, and congestive heart failure are the main clinical features of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, we hypothesized that in TDT patients, the tissue iron deposition could promote the neuronal cells death determining a thinning in ganglion cell complex and retinal nerve fiber layer, confirmed by the close correlation between the increased ferritin levels and the reduced thickness of the retinal nerve fiber layer [ 28 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 87%